1995
DOI: 10.1063/1.469630
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation dynamics of NO2 at moderately high energy (λ=309.1 nm; Eavail=7222 cm−1)

Abstract: The dynamics of NO2 dissociation at 309.1 nm have been explored by examining the nascent distribution of NO rotational, vibrational, spin–orbit, and lambda-doublet states. The NO fragment is produced with a monotonically decreasing vibrational distribution over the energetically accessible vibrational states (υ=0–3), and nonstatistical rotational distributions within each vibrational manifold. The distribution within υ=0 and 1 is strongly peaked near J=25.5 with a fairly narrow spread, the distribution within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Zacharias et al 7 observed a distribution in NO (v = 0-4) which showed little variation in the first four vibrational levels. These results were subsequently contradicted by Knepp et al 10 who photolysed a jet-cooled (T o 10 K) sample of NO 2 at 309.1 nm and found a monotonically decreasing population, which reflected a partitioning of energy significantly closer to statistical than the results of Zacharias et al 7 Doughty et al 11 obtained a vibrational distribution for NO (v = 1-3), using time resolved FTIR emission spectroscopy, which showed little significant variation in nascent populations for the first three vibrationally excited levels in reasonable agreement with Zacharias et al 7 Brouard et al 12 used the rotational distributions measured by Zacharias et al 7 and Knepp et al 10 to obtain nascent distributions for NO (v = 0-3) based on their O( 3 P) speed distributions from REMPI (2 + 1) velocity map ion imaging of the 308 nm photolysis of NO 2 . Using both data sets they present populations that are inverted at NO (v = 1) with vibrational populations inferred up to NO (v = 3).…”
Section: Introductionmentioning
confidence: 88%
“…Zacharias et al 7 observed a distribution in NO (v = 0-4) which showed little variation in the first four vibrational levels. These results were subsequently contradicted by Knepp et al 10 who photolysed a jet-cooled (T o 10 K) sample of NO 2 at 309.1 nm and found a monotonically decreasing population, which reflected a partitioning of energy significantly closer to statistical than the results of Zacharias et al 7 Doughty et al 11 obtained a vibrational distribution for NO (v = 1-3), using time resolved FTIR emission spectroscopy, which showed little significant variation in nascent populations for the first three vibrationally excited levels in reasonable agreement with Zacharias et al 7 Brouard et al 12 used the rotational distributions measured by Zacharias et al 7 and Knepp et al 10 to obtain nascent distributions for NO (v = 0-3) based on their O( 3 P) speed distributions from REMPI (2 + 1) velocity map ion imaging of the 308 nm photolysis of NO 2 . Using both data sets they present populations that are inverted at NO (v = 1) with vibrational populations inferred up to NO (v = 3).…”
Section: Introductionmentioning
confidence: 88%
“…65,67,68,74 The fragment rotational distributions tend to unimodal profiles which peak with moderate degrees of fragment rotational excitation as the excess energy in the (1) 2 B 2 state is increased. The photoproduct internal state distributions have been measured right across the first electronic absorption feature in a variety of experiments 46,[74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] which with the observation of interference or stepwise changes in dissociation timescale with excitation energy 59,60,62,94,95 provide support for the dissociation mechanism outlined above.…”
Section: Valence-valence Transitionsmentioning
confidence: 98%
“…near DO is modest (<1 per cm-1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Since in addition the number of product channels is relatively small, at least at low excess energies I?, quantum state-specific effects are expected. Above DO the spectrum of NO2, which remains highly structured, can be described in terms of coherently overlapping resonance^.^^^,^^ The state-selected resonance widths gradually increase with I?,7 as the dissociation lifetime decreases from a few picosecond just above DO to 1 ps at E?…”
Section: Introductionmentioning
confidence: 99%